MOF-based composite material, method for detecting VC through catalytic oxidation of TMB by using MOF-based composite material and application of MOF-based

The composite structure of Fe3O4@MOF@Au nanoparticles catalyzed oxidation of TMB to generate and fix hydrophilic ox-TMB, which solves the problems of limited catalytic activity and poor stability of nanoenzyme materials, and achieves high sensitivity detection of ascorbic acid VC.

CN119588427APending Publication Date: 2025-03-11洛兮生命科技(杭州)有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411791233.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing nanoenzyme materials have problems such as limited catalytic activity, poor stability, and difficulty in achieving effective binding and fixation with the detection substrate during the detection process, especially in complex environments.

Method used

Fe3O4@MOF@Au nanoparticles are used as catalysts to achieve efficient catalytic oxidation of TMB through the composite structure of Fe3O4 core, MOF shell and Au nanoparticles, and hydrophilic ox-TMB is generated and fixed on paper-based materials. The concentration of ascorbic acid VC is detected by color changes.

Benefits of technology

The catalytic reaction rate and conversion rate are significantly improved, and the low concentration of VC can be detected more sensitively. The detection method is simple and easy to use, without the need for complex instruments and data processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588427A_ABST
    Figure CN119588427A_ABST
Patent Text Reader

Abstract

The invention provides an MOF-based composite material, a method for detecting VC through catalytic oxidation of TMB by using the MOF-based composite material and application of the MOF-based composite By preparing the Fe3O4 (at) MOF (at) Au nano material, efficient catalytic oxidation of the TMB is realized. According to the method, a composite structure of Fe3O4, MOF and Au is utilized, so that the catalytic efficiency and sensitivity are improved, and low-concentration VC can be detected more sensitively. By oxidizing TMB into ox-TMB and fixing the ox-TMB on the paper-based material, the concentration change of VC is directly observed by using the color change, so that the simple and convenient detection method is realized. The method has a wide application prospect in the field of chemical analysis and detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of analytical chemistry, and particularly relates to a MOF-based composite material and a method and application thereof for detecting VC by catalytic oxidation of TMB. Background Art

[0002] In the biomedical field, sensitive and rapid detection of specific chemicals (such as ascorbic acid, i.e. vitamin C, VC) is of great significance. Traditional detection methods, such as spectroscopy, electrochemistry, and chromatography, although with high accuracy, often have limitations such as complex operation, high cost, and the need for specialized equipment. In recent years, nanozymes, as a new type of biomimetic material, have shown great potential in the field of biosensing and detection due to their unique catalytic properties and stability.

[0003] As a porous crystalline material, MOF (metal organic framework) has shown great potential in the field of catalytic oxidation in recent years. It is formed by self-assembly of metal ions or metal clusters and organic ligands and has a three-dimensional porous structure. This structural feature gives MOF a high specific surface area, regular pore structure and adjustable chemical composition, providing an ideal place for catalytic oxidation reactions. Among them, the metal sites in MOF can activate oxygen; the porous structure enables it to adsorb and enrich substrate molecules, increase the contact opportunities between the substrate and the active center, and thus improve the catalytic efficiency. These characteristics make MOF catalytic oxidation materials have broad application prospects in the controllable transport and release systems of drugs, dyes, and sensitive reagents such as enzymes and proteins, as well as highly selective catalysts or catalyst carriers.

[0004] However, there are still some problems in the preparation and application of existing nanozyme materials. For example, a single nanozyme material often has limited catalytic activity and is difficult to meet the needs of high-sensitivity detection; at the same time, the stability of the nanozyme material is also a key factor affecting its application effect. In addition, when applying nanozyme materials to actual detection, how to achieve effective binding and fixation with the detection substrate, and how to maintain its catalytic activity in a complex environment are also technical difficulties currently faced. Summary of the invention

[0005] Based on the above technical problems, the present invention proposes a MOF-based composite material and a method and application thereof for catalytic oxidation of TMB to detect VC. The present invention is achieved through the following technical solutions:

[0006] A MOF-based composite material, wherein the MOF-based composite material is Fe3O4@MOF@Au nanoparticles, which are composed of a Fe3O4 core, a MOF shell, and Au nanoparticles attached to the surface of the MOF shell; the MOF-based composite material Fe3O4@MOF@Au nanoparticles are used for catalytic oxidation of TMB to detect ascorbic acid VC, and exhibits peroxidase activity during the catalytic process, oxidizing hydrophobic TMB into hydrophilic ox-TMB;

[0007] The preparation method of the MOF-based composite material Fe3O4@MOF@Au nanoparticles comprises the following steps:

[0008] a) preparing Fe3O4 core by reacting FeCl3·6H2O, anhydrous ammonium acetate and EDTA-2Na in ethylene glycol, wherein the reaction molar ratio of FeCl3·6H2O: anhydrous ammonium acetate: EDTA-2Na and ethylene glycol is 0.056: 0.024: 0.001: 0.84;

[0009] b) in situ growth of a MOF shell on the surface of the Fe3O4 core, which is prepared by self-assembly of trimesic acid and Fe ions on the surface of the Fe3O4 core, wherein the reaction molar ratio of trimesic acid to Fe3O4 is 0.001:0.00075;

[0010] c) Fe3O4@MOF@Au nanoparticles were prepared by reducing HAuCl4 and depositing it on the surface of Fe3O4@MOF shell;

[0011] The pH stability of the MOF-based composite material Fe3O4@MOF@Au nanoparticles is between 5.5 and 8.5.

[0012] A method for detecting VC by catalytic oxidation of TMB using a MOF-based composite material comprises the following steps:

[0013] (1) Preparation of Fe3O4@MOF@Au nanomaterials:

[0014] S1: 15 g of FeCl3·6H2O was completely dissolved in 50 mL of ethylene glycol. Then, 1.5 g of anhydrous ammonium acetate (NH4OAc) and 0.4 g of EDTA-2Na were added to the mixed solution in sequence. Finally, the mixture was washed three times with deionized water and ethanol respectively, and dried at 50°C under vacuum for 16 hours to obtain Fe3O4 nanoparticles.

[0015] S2: With Fe3O4 nanoparticles as the core, 60 mg of Fe3O4 nanoparticles were dispersed in 5 mL of FeCl3·6H2O-ethanol solution (15 mM) by ultrasound (50 kHz, 8 min), and then 5 mL of trimesic acid (H3BTC)-ethanol solution (15 mM) was added. The mixture was stirred at 200 rpm for 20 min, washed three times with ethanol, and the precipitate was dried at 50 °C for 4 h to collect Fe3O4@MOF nanoparticles.

[0016] S3: HAuCl4 (0.8 μL, 12 mM) was added to 5 mL ethylene glycol solution containing 0.05 g PVP, and the mixture was placed in a 120°C environment and stirred magnetically for 4 hours to obtain gold nanoparticles. Subsequently, 60 mg of Fe3O4@MOF nanoparticles prepared in step S2 were added to 1.5 mL of gold nanoparticle solution under stirring and reacted for 8 hours under N2 protection, washed three times with ethanol, and the final precipitate was placed at 50°C and dried for 4 hours to collect the obtained Fe3O4@MOF@Au nanocomposite material.

[0017] (2) Pre-oxidation of TMB and fixation of ox-TMB: Take 3 mg of Fe3O4@MOF@Au nanozyme material and disperse it in 10 mL of 70% ethanol solution. Add an equal volume of 10 mM TMB-ethanol solution to the nanozyme solution. Under stirring at room temperature, use the nanozyme oxidation property of Fe3O4@MOF@Au to oxidize TMB into ox-TMB. React for 10 minutes to completely convert TMB into ox-TMB. Add 10 uL of the oxidized solution (containing ox-TMB and nanozyme) onto a hydrophilic paper-based material (nitrocellulose membrane). Using the hydrophilicity of the paper-based material, ox-TMB is evenly distributed on the paper surface and fixed by natural drying or heat drying. After drying, a thin film containing ox-TMB is formed on the paper-based material.

[0018] (3) Determination of ascorbic acid concentration: The paper-based material containing ox-TMB is immersed in a solution containing different concentrations of ascorbic acid (VC). Ascorbic acid reacts with ox-TMB to reduce ox-TMB to TMB, causing the blue color on the paper-based material to become lighter. The degree of color change is quantified by observing the color change or using image analysis technology (such as grayscale value measurement). A linear equation is established based on the relationship between the grayscale value of the blue color before and after the change and the VC concentration. Using the established linear equation, the concentration of ascorbic acid in the sample is indirectly determined based on the color change caused by the sample to be tested.

[0019] Preferably, while ensuring the consistency of shooting conditions, first, the color of ox-TMB on the surface of the paper-based material after being oxidized by Fe3O4@MOF@Au nanozyme is recorded as P1 (blue), and then the color of ox-TMB on the surface of the paper-based material reduced by the test substance VC is recorded as TMB as P2 (gray), and the grayscale values ​​of P1 and P2 are analyzed using Image J software, and the grayscale value difference of P2-P1 is recorded as ΔR, which is linearly correlated with the VC concentration.

[0020] The specific principle of the MOF-based composite material prepared by the present invention to detect VC by catalytic oxidation of TMB is as follows: hydrophobic TMB is oxidized to hydrophilic ox-TMB under the catalysis of Fe3O4@MOF@Au, so that it can be naturally fixed on the hydrophilic paper-based material-nitrocellulose membrane. The ox-TMB on the surface of the nitrocellulose membrane is reduced to TMB when encountering ascorbic acid (VC), and the blue color becomes lighter. Through TMB-ox-TMB-TMB, the gray value of the blue color before and after the change indirectly determines the specific concentration of VC.

[0021] Beneficial effects:

[0022] The present invention achieves efficient catalytic oxidation of TMB by finely regulating the composite structure of Fe3O4, MOF and Au. Compared with traditional natural enzyme catalysts, the reaction rate and conversion rate are significantly improved, and low concentrations of VC can be detected more sensitively, so that accurate measurement can be achieved in a low concentration range. By utilizing the nanozyme catalytic performance of Fe3O4@MOF@Au, hydrophobic TMB is converted into hydrophilic ox-TMB and fixed on the paper-based material, and the concentration change of VC can be directly observed by color change, without the need for complex instruments and data processing, making the detection method simpler and easier. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The transmission electron microscopy characterization results of the nanomaterials prepared in step S1, step S2, and step S3 of Example 1 are respectively, Figure 1 a is a transmission electron microscope characterization image of Fe3O4 prepared in step S1; Figure 1 b is the transmission electron microscopy characterization image of Fe3O4@MOF prepared in step S2; Figure 1 c is the transmission electron microscopy characterization image of Fe3O4@MOF@Au prepared in step S3; scale bar: 100 nm.

[0024] Figure 2 The dynamic light scattering particle size characterization results of the nanomaterials prepared in step S1, step S2, and step S3 of Example 1.

[0025] Figure 3 To study the peroxidase-like activity of Fe3O4@MOF@Au; Figure 3a is the absorbance results of Fe3O4 nanoparticles, Fe3O4@MOF nanoparticles and Fe3O4@MOF@Au nanoparticles with the same particle concentration; Figure 3 b is the absorbance value at 650 nm after Fe3O4 nanoparticles, Fe3O4@MOF nanoparticles and Fe3O4@MOF@Au nanoparticles catalyzed TMB.

[0026] Figure 4 The catalytic performance of VC was detected by oxidizing TMB using the MOF-based composite material prepared in the present invention under different pH conditions.

[0027] Figure 5 The catalytic performance of VC was detected by oxidizing TMB using the MOF-based composite material prepared in the present invention under different temperature conditions.

[0028] Figure 6 The catalytic performance of VC in oxidizing TMB was detected by using the MOF-based composite material prepared in the present invention at different storage times.

[0029] Figure 7 Schematic diagram of the contact angle of TMB / ox-TMB droplets on paper-based materials; Figure 7 a is a schematic diagram of the contact angle of TMB droplets on paper-based materials; Figure 7 b is a schematic diagram of the contact angle of ox-TMB droplets on paper-based materials.

[0030] Figure 8 The MOF-based composite material prepared by the present invention has the detection performance of VC by catalytic oxidation of TMB.

[0031] Fig. 9 The results are the experimental results of the detection specificity of VC by catalytic oxidation of TMB using the MOF-based composite material prepared in the present invention. DETAILED DESCRIPTION

[0032] The technical solution proposed in the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. Unless otherwise specified in the following embodiments, the technical means used in the embodiments of the present invention are conventional means well known to those skilled in the art.

[0033] Example 1: Preparation of Fe3O4@MOF@Au

[0034] S1: 15 g of FeCl3·6H2O was completely dissolved in 50 mL of ethylene glycol. Then, 1.5 g of anhydrous ammonium acetate (NH4OAc) and 0.4 g of EDTA-2Na were added to the mixed solution in sequence. Finally, the mixture was washed three times with deionized water and ethanol respectively, and dried at 50°C under vacuum for 16 hours to obtain Fe3O4 nanoparticles.

[0035] S2: With Fe3O4 nanoparticles as the core, 60 mg of Fe3O4 nanoparticles were dispersed in 5 mL of FeCl3·6H2O-ethanol solution (15 mM) by ultrasound (50 kHz, 8 min), and then 5 mL of trimesic acid (H3BTC)-ethanol solution (15 mM) was added. The mixture was stirred at 200 rpm for 20 min, washed three times with ethanol, and the precipitate was dried at 50 °C for 4 h to collect Fe3O4@MOF nanoparticles.

[0036] S3: HAuCl4 (0.8 μL, 12 mM) was added to 5 mL ethylene glycol solution containing 0.05 g PVP, and the mixture was placed in a 120°C environment and reacted with magnetic stirring for 4 h to obtain gold nanoparticles. Subsequently, 60 mg of Fe3O4@MOF nanoparticles prepared in step S2 were added to 1.5 mL of gold nanoparticle solution under stirring, and reacted for 8 h under N2 protection, washed three times with ethanol, and the final precipitate was placed at 50°C and dried for 4 hours to collect the obtained Fe3O4@MOF@Au nanocomposite material.

[0037] Example 2: Morphological characterization of Fe3O4@MOF@Au

[0038] The surface structure of Fe3O4@MOF@Au nanocomposites was observed using transmission electron microscopy. Before the measurement, Fe3O4@MOF@Au materials were dispersed in anhydrous ethanol, and then the dispersion was cast on a carbon film-coated copper grid.

[0039] Figure 1 The characterization results of the nanomaterials prepared in step S1, step S2, and step S3 of Example 1 are shown in FIG. Figure 1 As shown in a, the prepared Fe3O4 nanoparticles have a highly uniform morphology. Subsequently, the Fe3O4 nanoparticles prepared in step S1 were used as the core of the in-situ growth of MOF of MIL-100(Fe), which is equivalent to preparing Fe3O4@MOF nanostructures using a one-pot method. Figure 1The TEM image of b shows that Fe3O4@MOF has a clear core-shell structure, and the magnetic core is surrounded by an iron shell with an average thickness of about 40nm, indicating that MIL-100(Fe) is successfully coated on the surface of Fe3O4 nanoparticles. Then the Au nanoparticles prepared in step S3 are coated on the surface of Fe3O4@MOF prepared in step S2. The TEM image ( Figure 1 c) shows that high-density Au nanoparticles are uniformly distributed on the surface of Fe3O4@MOF, indicating the successful loading of Au nanoparticles.

[0040] Example 3: Particle size characterization of Fe3O4@MOF@Au

[0041] The Fe3O4 nanoparticles prepared in step S1 of Example 1, the Fe3O4@MOF nanoparticles prepared in step S2, and the Fe3O4@MOF@Au nanomaterials prepared in step S3 were analyzed by dynamic light scattering. Figure 2 As shown, the average size diameter of the Fe3O4 nanoparticles is about 180nm; after the MOF structure is formed, the average size diameter increases by about 40nm, which is consistent with the TEM results of Example 2, indicating the formation of a core-shell structure and the successful preparation of Fe3O4@MOF. Due to the small size of the gold nanoparticles prepared in step S3, the size of the Fe3O4@MOF@Au is only slightly larger than that of Fe3O4@MOF. From the DLS results, the size of the Au nanoparticles loaded on the outer layer of Fe3O4@MOF is about 5nm. The results of dynamic light scattering not only verify the changes in the size of the nanomaterials during each step of the synthesis process, but also further confirm that the gold nanoparticles are successfully attached to the surface of Fe3O4@MOF, forming the expected Fe3O4@MOF@Au ternary composite structure, and the structure maintains good dispersibility and small particle size growth.

[0042] Example 4: Study on the peroxidase-like activity of Fe3O4@MOF@Au

[0043] In order to study the peroxidase-like performance of Fe3O4@MOF@Au nanoparticles, a colorimetric experiment based on the oxidation of peroxidase TMB substrate by H2O2 was performed on the prepared Fe3O4@MOF@Au. H2O2 (30wt%, 20μL) and DMSO solution of TMB (15mM, 20μL) were mixed with acetate buffer solution (0.2M, 3mL, pH=3.6), and then 70% ethanol dispersion of Fe3O4@MOF@Au (2mg / mL, 20μL) was dispersed into the above solution. After incubation for 10 minutes, the absorbance at 650nm wavelength of UV-visible spectrum was measured to evaluate the catalytic activity of Fe3O4@MOF@Au.

[0044] In order to fully understand the peroxidase catalytic properties of Fe3O4 nanoparticles, Fe3O4@MOF and Fe3O4@MOF@Au, the ability to oxidize 3,3',5,5'-tetramethylbenzidine (TMB) in the presence of H2O2 was compared. Horseradish peroxidase (HRP) was used as a reference for the same catalytic oxidation reaction. Figure 3 As shown in the figure, without catalytic reaction, the absorbance of Fe3O4 nanoparticles, Fe3O4@MOF nanoparticles and Fe3O4@MOF@Au nanoparticles with the same particle concentration gradually increased, indicating that some properties of the nanomaterials were improved with the coating of MOF shell and gold nanoparticles ( Figure 3 a).

[0045] like Figure 3 As shown in Figure b, when the absorbance value was measured at a wavelength of 650 nm, the detection concentration of Fe3O4 nanoparticles dropped to 78.02 fM, the detection concentration of Fe3O4@MOF nanoparticles dropped to 39.01 fM, and the detection concentration of Fe3O4@MOF@Au nanoparticles dropped to 0.3 fM, confirming the excellent performance of Fe3O4@MOF@Au nanocomposite materials in peroxidase mimicking.

[0046] Example 5: Stability study of Fe3O4@MOF@Au nanozyme material

[0047] (1) pH stability: The Fe3O4@MOF@Au nanozyme material was dispersed in buffer solutions of pH 5.5, pH 6, pH 7, pH 8, and pH 8.5 to oxidize TMB. After incubation for 10 minutes, the absorbance of the UV-visible spectrum at a wavelength of 650 nm was measured to evaluate the catalytic activity of the Fe3O4@MOF@Au nanozyme material under different pH conditions.

[0048] When evaluating the catalytic activity of Fe3O4@MOF@Au nanozyme materials under different pH values ​​(pH5.5, pH6, pH7, pH8, pH8.5), we found that as the pH value gradually increased, the absorbance value of the nanozyme material at 650nm wavelength in the UV-visible spectrum did not fluctuate significantly ( Figure 4). Specifically, from acidic environment (pH5.5) to weak alkaline environment (pH8.5), the absorbance value remained in a relatively stable range, with only minor changes observed. These changes may be attributed to the weak effect of pH itself on the substrate TMB, rather than substantial changes in the catalytic performance of the nanozyme material. This result shows that the Fe3O4@MOF@Au nanozyme material can maintain its efficient catalytic activity over a wide pH range and is not significantly affected by changes in pH. The Fe3O4@MOF@Au nanozyme material can maintain good activity at different pH values, indicating that it has excellent stability.

[0049] (2) Temperature stability: The Fe3O4@MOF@Au nanozyme material was dispersed in a buffer solution to oxidize TMB and placed in an environment of 4°C, 25°C, 37°C, 50°C, and 70°C. After incubation for 10 minutes, the absorbance of the UV-visible spectrum at a wavelength of 650 nm was measured to evaluate the catalytic activity of the Fe3O4@MOF@Au nanozyme material under different temperature conditions.

[0050] By measuring the absorbance of the UV-visible spectrum at a wavelength of 650nm, Figure 5 As shown in the figure, the results show that the catalytic activity of Fe3O4@MOF@Au nanozyme material maintained a relatively high level under various temperature conditions (4℃, 25℃, 37℃, 50℃, 70℃). Specifically, from the low temperature of 4℃ to the physiological temperature of 37℃, the absorbance value showed a slight upward trend, which may be due to the intensification of molecular motion with the increase in temperature, thereby promoting the effective contact and reaction between the substrate TMB and the nanozyme material. Even at higher temperatures of 50℃ and 70℃, although the increase in the absorbance value slowed down, it still maintained at a high level overall, and there was no significant decline or inactivation. It shows that Fe3O4@MOF@Au nanozyme material can still maintain its structural stability and catalytic activity under high temperature conditions. Unlike natural enzymes, Fe3O4@MOF@Au nanozyme is not easily denatured or inactivated due to temperature increase. In summary, Fe3O4@MOF@Au nanozyme material can maintain good activity at different temperatures, indicating that it has excellent stability.

[0051] (3) Long-term storage stability: The Fe3O4@MOF@Au nanozyme material was stored at 4°C and room temperature, and its activity was measured weekly to observe the changes in activity over time.

[0052] like Figure 6The experimental results show that the catalytic activity of the Fe3O4@MOF@Au nanozyme material remains highly stable over time, whether under low-temperature storage conditions of 4°C or at room temperature. Specifically, under low-temperature storage conditions of 4°C, after four consecutive weeks of monitoring, the catalytic activity of the Fe3O4@MOF@Au nanozyme material has hardly changed, and the absorbance value remains constant at a wavelength of 650nm in the UV-visible spectrum, indicating that low temperature effectively slows down the rate of chemical reactions that may cause the material to inactivate, thereby extending the stable storage period of the material. Under room temperature conditions, although the absorbance value fluctuates slightly over time, it remains within a relatively stable range as a whole, and the fluctuation range is far less than the threshold that may cause a significant decrease in performance in practical applications. In summary, the Fe3O4@MOF@Au nanozyme material can maintain good catalytic activity during long-term storage, whether under low temperature or room temperature conditions, and exhibits excellent long-term storage stability.

[0053] Example 6: Pre-oxidation of TMB and fixation of ox-TMB

[0054] 3 mg of Fe3O4@MOF@Au nanozyme material was dispersed in 10 mL of 70% ethanol solution. An equal volume of 10 mM TMB-ethanol solution was added to the nanozyme solution. Under stirring at room temperature, the nanozyme oxidation performance of Fe3O4@MOF@Au was used to oxidize TMB into ox-TMB. The reaction lasted for 10 minutes to completely convert TMB into ox-TMB.

[0055] 10uL of the oxidized solution (containing ox-TMB and nanozymes) is dropped onto the hydrophilic paper-based material (nitrocellulose membrane). The hydrophilicity of the paper-based material is used to evenly distribute ox-TMB on the paper surface and fix it by natural drying or heat drying. After drying, a thin film containing ox-TMB is formed on the nitrocellulose membrane.

[0056] Example 7: Contact angle measurement of TMB and ox-TMB

[0057] An optical contact angle tester was used, the water drop volume was set to 5 μL, and the sample was placed flat on the platform. Through microcomputer control, TMB droplets and ox-TMB droplets were added to the surface of the paper-based material sample to test the contact angle. At least three sets of data were measured for each sample.

[0058] Figure 7 a is the morphology of TMB droplets on the surface of hydrophilic paper-based materials, with a contact angle of 136°, indicating that TMB is indeed hydrophobic. However, once the ox-TMB droplets touch the surface of hydrophilic paper-based materials, they spread out rapidly, and the contact angle can be regarded as zero ( Figure 7b), accompanied by part of the droplets being absorbed into the pores, which is related to the porous capillary phenomenon of the paper-based material, indicating that the hydrophobic TMB is converted into hydrophilic ox-TMB under the catalytic oxidation of Fe3O4@MOF@Au nanozyme.

[0059] Example 8: Determination of ascorbic acid concentration

[0060] Ascorbic acid (VC) standard solutions with concentrations of 0, 50, 150, 200, 250, 300, 400, 500, 600, 800, 1000, 1200, 1400, 1600 μM were prepared respectively, and the paper-based material containing ox-TMB, the color of which was recorded as P1, was immersed in VC solutions containing different concentrations. Ascorbic acid reacted with ox-TMB (blue) to reduce ox-TMB to TMB (gray), and the color was recorded as P2. The gray values ​​of P1 and P2 were analyzed by Image J software, and the gray value difference of P2-P1 was recorded as ΔR. According to the relationship between ΔR and VC concentration, a linear equation was established to determine the detection range and detection limit of Fe3O4@MOF@Au prepared by the present invention for preparing paper-based sensing materials for catalytic oxidation of TMB to detect VC.

[0061] The Fe3O4@MOF@Au nanozyme material prepared by the present invention was used to pre-oxidize TMB into hydrophilic ox-TMB, and then fixed on a nitrocellulose membrane for VC content analysis. Figure 8 As shown in FIG. 1 , this method establishes a linear relationship between VC concentration and gray value change. The VC concentration range is 5 to 1000 μM, and the linear equation is ΔR = 0.08647C VC +4.89833, correlation coefficient R 2 The detection limit was 0.993 and 1.707 μM.

[0062] Example 9: Study on the specificity of Fe3O4@MOF@Au nanozyme material in detecting VC

[0063] Prepare the paper-based material containing ox-TMB and ensure that it is evenly coated and dried. Prepare a series of ascorbic acid (VC) solutions with known concentrations and solutions containing different concentrations of interfering substances (Na + , K + , Ca 2+ , lactic acid, urea, glucose). + , K + , Ca 2+ Solutions of ox-TMB (e.g., lactic acid, urea, glucose) are mixed with a fixed concentration of ascorbic acid solution and then dropped or dipped onto a paper-based material containing ox-TMB. The color change is recorded and the extent of the color change is quantified using image analysis techniques (e.g., gray value measurement).

[0064] Taking into account the competitive interferences (such as Na + , K + , Ca 2+ , lactic acid, urea) may interfere with the test results. The above substances were used to specifically analyze the VC content of the Fe3O4@MOF@Au nanozyme material prepared by the present invention. The results are as follows Fig. 9 As shown, Na + , K + , Ca 2+ , lactic acid, urea, glucose, etc. The response values ​​are much lower than those of VC, indicating that the Fe3O4@MOF@Au nanozyme material prepared by the present invention has a high specificity in detecting VC content.

Claims

1. A MOF-based composite material, characterized in that: The MOF-based composite material is Fe3O4@MOF@Au nanoparticles, which are composed of Fe3O4 cores, MOF shells, and Au nanoparticles attached to the surface of the MOF shells; the MOF-based composite material Fe3O4@MOF@Au nanoparticles are used for catalytic oxidation of TMB to detect ascorbic acid VC, and exhibit peroxidase activity during the catalytic process, oxidizing hydrophobic TMB into hydrophilic ox-TMB; The preparation method of the MOF-based composite material Fe3O4@MOF@Au nanoparticles comprises the following steps: a) preparing Fe3O4 core by reacting FeCl3·6H2O, anhydrous ammonium acetate and EDTA-2Na in ethylene glycol, wherein the reaction molar ratio of FeCl3·6H2O: anhydrous ammonium acetate: EDTA-2Na and ethylene glycol is 0.056: 0.024: 0.001: 0.84; b) in situ growth of a MOF shell on the surface of the Fe3O4 core, which is prepared by self-assembly of trimesic acid and Fe ions on the surface of the Fe3O4 core, wherein the reaction molar ratio of trimesic acid to Fe3O4 is 0.001:0.00075; c) Fe3O4@MOF@Au nanoparticles were prepared by reducing HAuCl4 and depositing it on the surface of Fe3O4@MOF shell; The pH stability of the MOF-based composite material Fe3O4@MOF@Au nanoparticles is between 5.5 and 8.

5.

2. An application of the MOF-based composite material as claimed in claim 1 in catalytic oxidation of TMB to detect VC, characterized in that: The composite material is dispersed in an ethanol solution, TMB-ethanol solution is added, and the mixture is stirred at room temperature to oxidize the hydrophobic TMB into the hydrophilic ox-TMB, and then the concentration of VC is determined by the color change or by quantifying the extent of the color change using image analysis technology.

3. The use according to claim 2, characterized in that: A solution containing ox-TMB was dropped onto a hydrophilic nitrocellulose membrane, and after drying, a thin film containing ox-TMB was formed. The nitrocellulose membrane was then immersed in solutions containing different concentrations of VC to observe the color change.

4. A method for detecting VC by catalytic oxidation of TMB by a MOF-based composite material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) Preparation of Fe3O4@MOF@Au nanomaterials: S1: 15 g FeCl3·6H2O was completely dissolved in 50 mL ethylene glycol, and 1.5 g anhydrous ammonium acetate NH4OAc and 0.4 g EDTA-2Na were added to the mixed solution in sequence; finally, the mixture was washed with deionized water and ethanol three times respectively, and dried at 50 °C under vacuum for 16 hours to obtain Fe3O4 nanoparticles; S2: With Fe3O4 nanoparticles as the core, 60 mg of Fe3O4 nanoparticles were dispersed in 5 mL of 15 mM FeCl3·6H2O-ethanol solution by 50 kHz ultrasound for 8 min, and then 5 mL of 15 mM trimesic acid H3BTC-ethanol solution was added, stirred at 200 rpm for 20 min, washed three times with ethanol, and the precipitate was dried at 50 °C for 4 h to collect Fe3O4@MOF nanoparticles; S3: Add 0.8 μL of 12 mM HAuCl4 solution to 5 mL of ethylene glycol solution containing 0.05 g of PVP, place the mixture in a 120°C environment, and react for 4 hours under magnetic stirring to obtain gold nanoparticles; then, add 60 mg of Fe3O4@MOF nanoparticles prepared in step S2 to 1.5 mL of gold nanoparticle solution under stirring, and react for 8 hours under N2 protection, wash three times with ethanol, and dry the final precipitate at 50°C for 4 hours to collect the obtained Fe3O4@MOF@Au nanocomposite material; (2) Pre-oxidation of TMB and fixation of ox-TMB: Take 3 mg of Fe3O4@MOF@Au nanozyme material and disperse it in 10 mL of 70% ethanol solution; add an equal volume of 10 mM TMB-ethanol solution to the nanozyme solution, and use the oxidation performance of Fe3O4@MOF@Au nanozyme to oxidize TMB into ox-TMB under stirring at room temperature. React for 10 minutes to completely convert TMB into ox-TMB. Add 10uL of the oxidized solution containing ox-TMB and nanozyme onto a hydrophilic nitrocellulose membrane; use the hydrophilicity of the paper-based material to evenly distribute ox-TMB on the paper surface and fix it by natural drying or heat drying; after drying, a thin film containing ox-TMB is formed on the paper-based material; (3) Determination of ascorbic acid concentration: The paper-based material containing ox-TMB is immersed in a solution containing different concentrations of ascorbic acid VC; ascorbic acid reacts with ox-TMB to reduce ox-TMB to TMB, causing the blue color on the paper-based material to become lighter; the degree of color change is quantified by observing the color change or using grayscale value measurement, and a linear equation is established based on the relationship between the grayscale value of the blue color before and after the change and the VC concentration. Using the established linear equation, the concentration of ascorbic acid in the sample is indirectly determined based on the color change caused by the sample to be tested.

5. The method according to claim 4, characterized in that The method for determining ascorbic acid described in step (3) is preferably, while ensuring the consistency of shooting conditions, first, recording the color of ox-TMB on the surface of the paper-based material after being oxidized by Fe3O4@MOF@Au nanozyme as P1-blue, and then recording the color of ox-TMB on the surface of the paper-based material reduced by the test substance VC as TMB as P2-gray, and using Image J software to analyze the grayscale values ​​of P1 and P2, and the grayscale value difference of P2-P1 is recorded as ΔR, which is linearly correlated with the VC concentration.

6. The method according to claim 4 or 5, characterized in that: The detection range of the VC concentration is 5 to 1000 μM; the linear equation is ΔR=0.08647C VC +4.89833, correlation coefficient R 2 The detection limit was 0.993 and 1.707 μM.

7. A kit for detecting VC, characterized in that: The invention comprises the MOF-based composite material according to claim 1 as a reagent for catalytic oxidation of TMB, a dropper for dripping a solution, a device for drying a paper-based material, and an image analysis device for measuring color changes.

8. The kit according to claim 7, characterized in that The paper-based material is a nitrocellulose membrane.